Ecofeminism from a Catholic perspective: (Study of Bandung Diocese's thought through Laudato Si) - Evi Fita Ulifia (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2022)
This study aims to understand the concept of ecofeminism through the study of Laudato Si from a Catholic perspective. This study uses a qualitative approach by applying descriptive analysis methods. Data collection techniques were carried out through library research and field studies on the Bandung Diocese of thought case. The formal object of this research is Laudato Si, a Catholic perspective on the thought of the Diocese of Bandung, while the material object of this research is ecofeminism. The results of the research and discussion in this study indicate that ecofeminism social movements that juxtapose the relationship between women and nature seem to have space and are openly accepted by Catholic teachings. Laudato Si is reflected in the thought of the Diocese of Bandung, which understands as an invitation to care for Mother Earth to maintain the ecosystem as a shared house. This study concludes that ecofeminism is in harmony with Laudato Si in a Catholic perspective through the thought of the Diocese of Bandung, which asserts that nature is the mother who gives birth and cares for life. This is a shared responsibility in maintaining the sustainability of nature and the environment.